2022
DOI: 10.3390/jcm11216465
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Stem-Cell Genes and Klotho in Atherosclerotic Aortas: Regulating Spatially Deranged Expression Patterns Using Colchicine Regimens

Abstract: Aims: Inflammatory dysregulation of mechanosensitive developmental genes may be central to atherogenesis. In the present seven-week model, we utilized colchicine regimens to curtail aortic atherogenesis in New Zealand White rabbits. We also explored the effect of colchicine regimens on atheroprotective (Klotho, HOXA5, NOTCH1, and OCT4) and proatherogenic (HIF1a, SOX2, BMP4, and NANOG) genes. Methods: The control (n = 6) and group A (n = 6) received standard and cholesterol-enriched chow, respectively. Groups B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Our analysis also extended into emerging atherosclerosis markers, such as klotho and pluripotency genes [6,7,[40][41][42][43][44]. Klotho is an anti-aging hormone that plays a pivotal role in the preservation of endothelial cell integrity [45][46][47].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our analysis also extended into emerging atherosclerosis markers, such as klotho and pluripotency genes [6,7,[40][41][42][43][44]. Klotho is an anti-aging hormone that plays a pivotal role in the preservation of endothelial cell integrity [45][46][47].…”
Section: Discussionmentioning
confidence: 94%
“…We recently conveyed that colchicine-based treatment can upregulate klotho levels in atherosclerotic aortic tissue [6]. While colchicine remains the sole FDA-approved immunomodulator targeting proatherogenic inflammation with effects on klotho levels (among other molecules) [55], our research presents a novel therapeutic pathway for consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TyG index also demonstrated superior predictive capabilities for MetS compared to HOMA-IR [ 63 ]. Moreover, a meta-analysis of 13 observational studies corroborated the TyG index's optimal sensitivity and specificity for MetS screening, suggesting its potential as a valuable alternative biomarker for clinical follow-up management in MetS populations [ 64 ]. Notably, a significant elevation in the TyG index was observed in young adults diagnosed with MetS [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has also revealed that the expression of various stem cell genes (including KLF4 (Krüppel-like factor 4), HOXA5, NANOG, and HIF1α (hypoxia-inducible factor 1-alpha)) can be dysregulated by shear stress [9][10][11]. These genetic alterations may potentially orchestrate specific patterns in venous graft failure, including the development of neointimal hyperplasia [12][13][14].…”
Section: Introductionmentioning
confidence: 99%